Diagnostics of skin features through 3D skin mapping based on electro-controlled deposition of conducting polymers onto metal-sebum modified surfaces and their possible applications in skin treatment - Fu, Xiaoxu (2021)
Analytical diagnostics of skin features was developed through application of portable and fast skin mapping based on electro-controlled deposition of conducting polymers onto metal-sebum modified surfaces. In this analytical diagnostic technique, the development of skin pattern is based on electropolymerization of conducting polymers within insulating barriers in skin stamp provided by natural sebum to monitor the 3D nature of various skin features. The recorded skin maps reach a μm-level resolution and are proved to be capable of recognition, enhancement, and reproduction of surface outlines of various skin topographies, subsequently assisting dermatological diagnosis. The technique can precisely record skin surface morphology and reflect the vertical dimension information within 10 min and is aimed to assist dermatologists working with patients suffering from skin diseases via recording or monitoring the skin surface conditions. Additionally, successful trials of loading and electro-controlled release of Cu²⁺ into/from the developed skin patterns reveals its potential to be also utilized for treatment of pathological skin conditions. Based on the developed analytical diagnostic technique, a well-designed 3D printed portable prototype device based on electrosynthesis of the conducting polymer powered by an ordinary battery (1.5 V) was tested and was found to have excellent performance in onsite 3D skin pattern reproduction from live human skin.